GE_GERICHTE P/13074/2018 vom 17. April 2023 - GE Cour de justice (2023)
IN DUBIO PRO REO;ABUS DE CONFIANCE;QUALITÉ POUR AGIR ET RECOURIR;AVOCAT;HONORAIRES | CPP.121.al1; CP.110.al1; CPP.382.al1; CPP.382.al3; CPP.389.al3; CPP.139.al2; CP.138.ch1.par2